The Effectiveness of community approach in solid waste management at household and street level in Tanzania: A case of Mbeya City Council - Nguge, Josephine F. (Mzumbe University, 2023)
A Dissertation Submitted to the Institute of Development Studies in Partial Fulfillment of the Requirements for the Award of the Master of Science Degree in Environmental Management (MSc. EM) of Mzumbe University.